Halliday and Chinese linguistics: the full circle - Hu, Zhuanglin 1933- (The M. A. K. Halliday Library functional linguistics series, 2024)
This book is a progressive exposition on Halliday's academic thought and its origins by the renowned linguist Hu Zhuanglin, based on 30 years of research. The first part, "Chinese Origin," introduces readers to the author's gradual understanding that Halliday's academic thought mainly came from Chinese scholars such as Wang Li, Luo Changpei, and Gao Mingkai. In 1980s, Halliday and his students introduced the theory of Systemic Functional Linguistics into the foreign language and linguistics circles in China; thus, Halliday's academic thought returned to where it originated. The second part, "A Discussion of Theories," mainly addresses the author's experience and further discussions after learning Halliday's theory. The theme of the third part is "Discourse Analysis" and focuses on the greatest difference between Systemic Functional Linguistics and traditional grammar—sentence grammar. Halliday emphasizes the study of "discourse," and sentences are only the embodiment of discourse atthe next level. The fourth part, "The Study of Chinese," applies Halliday's linguistic theory to the evolution of the research of the Chinese language in China, which can better explain the theme of "return" and is of great significance for Chinese scholars' understanding and application of Halliday's academic thought